An Investigation on Foreign Language Form 3 Students’ Perceptions On The Factors That Affect Their Motivation to Learn French at Saint Thomas High School in Trinidad And Tobago - Rampaul, Kezia (My University, 2017)
The study investigated six students' perceptions of the factors affecting their motivation to learn French at the Form 3 level at a secondary school in Trinidad and Tobago. Data were obtained through interviews. The findings revealed that the students' attitude, perceived competence, the perceived difficulty of French, and their perception of in-class learning activities affected their intrinsic motivation. Their extrinsic motivation for French language learning was affected by factors of: 1) grades, 2) instructional style of the teacher, 3) the relevance of French to their career path, 4) the importance of French in local society and 5) negative influence of family members.
Keywords: Case studies; Perception; French; Foreign language education; Secondary school students; Student attitudes; Trinidad and Tobago